Native plants of Northern Australia - Brock, John 1951- (New Holland, 2022)
Now Fully updated this new revised edition of Native Plants of Northern Australia with over 450 species are described, with 700 colour photographs. Covers the northern Northern Territory and the offshore islands. Each species is individually presented with photographs, extensive descriptive information and distribution maps. Aboriginal plant usage is also recorded, including food, craft, and medicinal uses
Previous ed.: 2007
"First published as 'Top end native plants' in 1988
Keywords: Verbreitungskarte; Pflanzengesellschaft; Gefäßpflanzen; Nordaustralien; Botany / Australia / Northern Territory; Endemic plants / Australia / Northern Territory; Plantes endémiques / Australie / Territoire du Nord; Botany; Endemic plants; Northern Territory / https://id.oclc.org/worldcat/entity/E39QbtfRx4M4JX3Cg9YBfk9MmM; Verzeichnis; Bildband